2022
DOI: 10.1039/d1ta08855f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh charge–discharge efficiency and high energy density of a high-temperature stable sandwich-structured polymer

Abstract: A new generation of high-temperature dielectric materials toward capacitive energy storage is highly demanded as power electronics are always exposed to elevated temperatures in high-power applications. Polymer dielectric materials, an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Average lower leakage current density indicates that the 2D BNNSs-TiO 2 nanofillers could substantially diminish the conductivity loss by effectively suppressing charge injection from the electrode/dielectric interface, and this charge blocking effect facilitates the electric field strength and dielectric properties. [59][60][61][62][63][64][65][66][67] Generally, the above simulation results are in conformance with the experimental results.…”
Section: Resultssupporting
confidence: 86%
“…Average lower leakage current density indicates that the 2D BNNSs-TiO 2 nanofillers could substantially diminish the conductivity loss by effectively suppressing charge injection from the electrode/dielectric interface, and this charge blocking effect facilitates the electric field strength and dielectric properties. [59][60][61][62][63][64][65][66][67] Generally, the above simulation results are in conformance with the experimental results.…”
Section: Resultssupporting
confidence: 86%
“…The influence of the trap layer location on the breakdown can be attributed to the shape characteristics of the breakdown path. In addition, the effect of trap parameters on the conductivity is explored, and the results showed that the trap density and location have Comparisons of U and the corresponding electric field of this work and other reported composites at 150 1C with 90% efficiency 1,3,4,9,10,12,13,25,29,[52][53][54][55][56][57][58][59][60][61]…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, the energy density of the best commercially available dielectric polymer, biaxially oriented polypropylene (BOPP), is relatively low of 2.2 J cm À3 at 500 MV m À1 , which is 1-2 orders of magnitude smaller than that of batteries (B 200-500 J cm À3 ). [10][11][12][13] Theoretically, an outstanding discharged energy density (U d ) of dielectric materials could be achieved through regulating electric displacement (D) and breakdown strength (E b ). [14][15][16][17] Therefore, the development of high-performance film capacitors is an enormous challenge for highly integrated and miniaturized electronic systems.…”
Section: Introductionmentioning
confidence: 99%